WNT5A: a motility-promoting factor in Hodgkin lymphoma - Linke, F; Zaunig, S; Nietert, M M; von Bonin, F; Lutz, S; Dullin, C; Janovská, P; Beissbarth, T; Alves, F; Klapper, W; Bryja, V; Pukrop, T; et al. (Oncogene, 2017)
Classical Hodgkin lymphoma (cHL) has a typical clinical manifestation, with dissemination involving functionally neighboring lymph nodes. The factors involved in the spread of lymphoma cells are poorly understood. Here we show that cHL cell lines migrate with higher rates compared with non-Hodgkin lymphoma cell lines. cHL cell migration, invasion and adhesion depend on autocrine WNT signaling as revealed by the inhibition of WNT secretion with the porcupine inhibitors Wnt-C59/IWP-2, but did not affect cell proliferation. While application of recombinant WNT5A or WNT5A overexpression stimulates HL cell migration, neither WNT10A, WNT10B nor WNT16 did so. Time-lapse studies revealed an amoeboid type of cell migration modulated by WNT5A. Reduced migration distances and velocity of cHL cells, as well as altered movement patterns, were observed using porcupine inhibitor or WNT5A antagonist. Knockdown of Frizzled5 and Dishevelled3 disrupted the WNT5A-mediated RHOA activation and cell migration. Overexpression of DVL3-K435M or inhibition of ROCK (Rho-associated protein kinase) by Y-27632/H1152P disrupted cHL cell migration. In addition to these mechanistic insights into the role of WNT5A in vitro, global gene expression data revealed an increased WNT5A expression in primary HL cells in comparison with normal B-cell subsets and other lymphomas. Furthermore, the activity of both porcupine and WNT5A in cHL cells had an impact on lymphoma development in the chick chorionallantoic membrane assay. Massive bleeding of these lymphomas was significantly reduced after inhibition of WNT secretion by Wnt-C59. Therefore, a model is proposed where WNT signaling has an important role in regulating tumor-promoting processes.
Keywords: Hodgkin Disease; Signal Transduction; proliferace buněk; dikobrazovití a urzonovití; Cell Line, Tumor; Humans; Frizzled Receptors; Gene Expression; lidé; počítačová rentgenová tomografie; Cell Movement; biopsie; Biopsy; exprese genu; Cell Proliferation; signální transdukce; Models, Biological; biologické modely; Wnt-5a Protein; Dishevelled Proteins; Animals; buněčná adheze; zvířata; pohyb buněk; protein Wnt 5a; nádorové buněčné linie; frizzled receptory; Hodgkinova nemoc; protein dishevelled; rhoA protein vázající GTP; Cell Adhesion; rhoA GTP-Binding Protein; Tomography, X-Ray Computed; Porcupines